2014
DOI: 10.1182/blood-2013-08-520445
|View full text |Cite
|
Sign up to set email alerts
|

Blood stem cell fate regulation by Delta-1–mediated rewiring of IL-6 paracrine signaling

Abstract: Key Points The Notch ligand Delta-1 reduces membrane bound IL-6R expression, inhibiting IL-6 cis-signaling and the production of myeloid cells. Combined with a dynamically fed culture system that minimizes IL-6 trans-signaling, Delta-1 produces rapid and sustained HSC engraftment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 34 publications
(45 reference statements)
0
22
0
Order By: Relevance
“…To understand the mechanism by which IL-1β affected KN6 cellularity, we analyzed the levels of IL-6, an inflammatory cytokine induced by IL-1β. IL-6 has been shown to inhibit the expansion of hematopoietic stem cells, in a manner which is blocked by Notch signaling 36 , bringing up the possibility that a similar mechanism could be at play in KN6/MEF co-cultures. Indeed, we found that any culture supplemented with IL-1β also contained high amounts of IL-6 protein, as assessed by ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…To understand the mechanism by which IL-1β affected KN6 cellularity, we analyzed the levels of IL-6, an inflammatory cytokine induced by IL-1β. IL-6 has been shown to inhibit the expansion of hematopoietic stem cells, in a manner which is blocked by Notch signaling 36 , bringing up the possibility that a similar mechanism could be at play in KN6/MEF co-cultures. Indeed, we found that any culture supplemented with IL-1β also contained high amounts of IL-6 protein, as assessed by ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to define and optimize culture conditions to maintain LTR cells. Ensuring the presence of clinically relevant HPC/mature cells in the UCB graft is stressed by Csaszar et al [14]. The authors suggested that, a 15 fold expansion of LTR HSC would enable patients up to 162 kg to receive a recommended cell dose of an unmanipulated unit if the HSC that are important for long term engraftment are present.…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%
“…A novel way of Notch ligand Delta 1 mediated expansion via IL-6 induction was recently described by Csaszar E and colleagues [14]. They describe the way Delta 1 alters cytokine receptor distributions on hematopoietic cells, altering feedback networks and their impact on stem cell fate.…”
Section: Notch Signaling Pathwaymentioning
confidence: 99%
See 2 more Smart Citations